Formative, Preformative, and Proformative Evaluation - Michael Scriven (Journal of MultiDisciplinary Evaluation)
Michael Scriven defines the terms 'preformative' and 'proformative' in the context of his thinking on evaluation types, such as in the Key Evaluation Checklist. The discussion works through formative, summative, and ascriptive evaluations, eventually introducing and providing examples of 'proformative evaluation' as an addition to the set of three.